Sêntimus: um jogo digital musical para crianças com hipersensibilidade sonora e característica dos transtornos do neurodesenvolvimento - Débora Line Gomes (2018)
Digital games have a growing production worldwide, especially in the entertainment sector. There is also a growing trend of using Serious Games (i.e. games whose primary mission is not entertainment) for health purposes. Serious Games use technology to capture body movements from mobile devices. The appropriation of the playful atmosphere of these applications, inserted in the context of technology and health, benefit the user who has at their disposal unconventional alternatives of intervention. In the context of this paper our focus is on games that support the treatment of children with Sound Hypersensitivity and Neurodevelopmental Disorders. Sound Hypersensitivity is characterized by a dysfunction in the processing of sound in the Central Nervous System, where the cochlea is perfectly normal in patients who complain of excessive irritation or pain related to certain sounds and common noise levels. Neurodevelopmental Disorders, according to the Diagnostic and Statistical Manual of Mental Disorders 5 (DSM-5), are defined as a group of irregular conditions that occur during development, even before the school period. In the search for musical games developed for children with Sound Hypersensitivity and Neurodevelopmental Disorders, we did not identify any research in this framework. For this reason, the objective of this dissertation is to present the development and evaluation of a serious digital music game specific to the population. For this, what was done in this work: 1) Survey of the user profile through a questionnaire answered by 35 participants; 2) Proposed strategies identified for the treatment of both pathologies and application in the game; 3) Evaluation of the proposed game that were performed on direct and indirect users. The indirect users selected were 5 professional music therapists dealing with the research population. Indirect users were 3 children aged 6 to 8 years with Neurodevelopmental Disorders and Mild Hypersensitivity with mild and moderate severity for both conditions. In accordance with the research ethics legislation, to evaluate the game we submitted the project to the Research Ethics Committee and was approved with number 77747917.8.0000.5149. Our methodology used the Intermediate Semiotic Inspection Method (MISI) for indirect users, which generated results on the therapeutic character of the game. As for the end user we used the Game Tracking Form created specifically for this research, which pointed out gameplay levels in player performance. In general, the results of the evaluations generated positive indicators on the use of Sentimus. Due to all the steps taken, in view of the exploratory and descriptive character, we consider that Sentimus may be appropriate for evaluation, treatment or entertainment of this population. We consider that the work brings both theoretical contributions to the strategies and the possibility of using the game for the treatment of this group, and practical with the direct use of the game itself.